Nursing and midwifery students’ knowledge and concerns about COVID-19: a descriptive-analytical study - Tahereh Najafi Ghezeljeh; Sahar Keyvanloo Shahrestanaki; Ali Abbasi; Fatemeh Ghonodi; Azita Emami (Intelektual Pustaka Media Utama, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has changed educational trends for all university students, including nursing and midwifery students (NMSs). In the future, these students will play critical roles in healthcare delivery systems. The purpose of the study was to examine knowledge, fear, and anxiety about COVID-19 among NMSs. A cross-sectional descriptive-analytical study involved 600 NMSs were performed through an online survey from February to March 2021 in Iran University of Medical Sciences. Data gathering was done using a demographic questionnaire, the COVID-related Knowledge Questionnaire, The Fear of COVID-19 Scale, and the Corona Disease Anxiety Scale. Instruments were provided to students through WhatsApp, Telegram, or email. The study instruments were completely answered by 415 students. Their age was 24.63±4.97 years, on average. Most participants were female (62.2%) and single (76.9%). The mean scores of their knowledge, fear, and anxiety about COVID-19 were respectively 13.41±1.32 (in the possible range of 0–15), 21.93±6.78 (in the possible range of 7–35), and 19.82±12.77 (in the possible range of 0–54). NMSs have great knowledge, relatively great fear, and mild anxiety about COVID-19. Flexible educational programs, close monitoring of fear and anxiety, and effective need-based education are necessary for NMSs, particularly during pandemics.